“The Latvian Dream” as a Meeting Space with the Other - Prusinowska, Justyna (Colloquia, 2017)
In Latvian literature, there is a dream (or vision or some other subconscious process) about Latvianness and Latvian national identity, which has repeatedly appeared for more than a few decades. The hero of this dream meets the Other and this confrontation allows him to recognize and understand himself, something that is difficult to achieve in a state of consciousness. The Other is not always a Black Knight in armour reflecting upon the life of an ordinary peasant; he can also be another Latvian, usually an (im) migrant – someone who sees the nation from a very different perspective. This article focuses on several literary works depicting this kind of extraordinary meeting while asleep or unconscious (the space of a dream, a projection, a fairy-tale or a fantasy journey) with a variously understood Other, including Wannem Ymanta (1802) by Garlieb Merkel, the epic Lāčplēsis (The Bear-Slayer, 1888) by Andrejs Pumpurs, Lāčplēsis trimdā (Lāčplēsis in exile, 1958/1986/1990) by Dzintars Sodums and Latviešu sapnis (Latvian dream, 2002) by Agnese Bule. All of these books were very important at key turning-points or difficult moments in Latvia’s history – the process of national awakening and identity-building always involved depicting the other face of the Other.